Pengaruh Penerapan Sistem Informasi Pemerintahan Daerah, Pengendalian Internal Dan Pemanfaatan Teknologi Informasi Terhadap Kualiatas Laporan Keuangan (Studi Pada Badan Pengelolaan Keuangan Dan Aset Daerah Kabupaten Jember) - April Dwi Wulandari; Anik Yuliati (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study is to determine and test emprirically the effect of the application of Regional Government Information Systems, Internal Control and Utilization of Information Technology on the quality of financial reports of the Regional Financial and Asset Management Agency (BPKAD) of Jember Regency. This research uses a quantitative approach, using primary data through questionnaires. The subjects of this study are employees who carry out accounting or financial administration functions who have worked for 2 years with a minimum of high school education in all majors. The sample in this study used no-probability sampling with a purposive sampling technique with a total of 45 samples that met the criteria. The analysis technique in this study used multiple linear regression analysis with assistance sofware IBM SPSS Statistics 26. The results of this study indicated that (1) the application of the Regional Government Information System has a significant positive effect on the quality of financial reports at the BPKAD of Jember Regency. (2) Internal control has a significant positive effect on the quality of financial reports at BPKAD Jember Regency. (3) Utilization of information technology has a significant positive effect on the quality of financial reports at BPKAD Jember Regency. Keywords: Regional Government Information System, Internal Control, Utilization of Information Technology, Quality of Financial Reports